Comparison of independent navigation of LNG carriers of type Yamalmax and their transition with an icebreaker escort - Sokolova Yu.V.; Devyataev O.S.; Afanasyeva E.V.; Titova Yu.M. (LLC Center for Information and Legal Support for the Development of the Arctic, 2020)
In May-June 2020 two early transits through the Northern Sea Route to the east were made by LNG carriers «Christophe de Margerie» and «Vladimir Voronin». The first voyage was accompanied by the nuclear icebreaker «Yamal» all the way down, the second voyage «Vladimir Voronin» covered independently. In this paper, on the example of the pair «Christophe de Margerie» and «Vladimir Voronin» and one more pair «Georgy Brusilov» and «Vladimir Rusanov», followed the pioneer tankers a month later, it was analyzed two types of navigation: independent and with an icebreaker escort. The results of the analysis did not reveal sufficient differences in time and velocity of tankers, navigating independently or under icebreaker escort in those ice conditions, which had developed by the beginning of summer navigational season.